Ex Vivo Microscopy: A Promising Next-Generation Digital Microscopy Tool for Surgical Pathology Practice - Krishnamurthy, Savitri (Arch Pathol Lab Med, 2019)
CONTEXT.—: The rapid evolution of optical imaging modalities in recent years has opened the opportunity for ex vivo tissue imaging, which has significant implications for surgical pathology practice. These modalities have promising potential to be used as next-generation digital microscopy tools for examination of fresh tissue, with or without labeling with contrast agents. OBJECTIVE.—: To review the literature regarding various types of ex vivo optical imaging platforms that can generate digital images for tissue recognition with potential for utilization in anatomic pathology clinical practices. DATA SOURCES.—: Literature relevant to ex vivo tissue imaging obtained from the PubMed database. CONCLUSIONS.—: Ex vivo imaging of tissues can be performed by using various types of optical imaging techniques. These next-generation digital microscopy tools have a promising potential for utilization in surgical pathology practice.